ANALISIS POTENSI DAN PEMANFAATAN PEMBANGKIT LISTRIK MIKROHIDRO (PLTMH) DI DESA TIPANG KECAMATAN BAKTI RAJA SUMATERA UTARA - Gunawan sihombing (Universitas Muhammadiyah Gresik, 2024)
Electrical energy is a basic need for society. The availability of electrical energy is one of the driving factors for improving the community's economy. However, the availability of electrical energy is not felt by the residents of Tipang Village. There are frequent power outages so that people sometimes go days without using electricity. Frequent power outages certainly disrupt community activities. One solution to overcome the electricity shortage is to use the waterfall channel to become a hydroelectric power plant. This power plant can be integrated with waterways to produce clean and sustainable electrical energy. The aim of this research is to calculate the flow rate of the water channel (river) in the Janji waterfall channel in Tipang Village, then analyze the energy potential of the river water flow around the Janji waterfall channel in Tipang Village. The results of the research are that the measured discharge of the Janji River, Tipang Village, Bakti Raja District is around 400 s/d. 600 liters per second and an average height of 35 m. Tipang Village's potential for a micro-hydro power plant (PLTMH) is 80 kW. If you use one Turbo Propeller type turbine (horizontal axis), 300 mm diameter and 1 3-phase synchronous generator unit, it can produce 35 kW of electricity from this potential, which can meet the electricity needs of the people of Tipang Village, Humbang Hasundutan Regency.